The Leadership of the CPC and the Great Rejuvenation of the Chinese Nation - ZHU , Lingli (Journal of Social Science Studies, 2021)
To realize the great rejuvenation of the Chinese nation, we must adhere to the leadership of the CPC. The nature and purpose of the Party determine that only by adhering to the leadership of the CPC can we organize and mobilize the people, create a stable environment, and finally achieve the glorious goal of people's happiness. Guided by Marxism, the CPC constantly promotes theoretical innovation, which can gather the ideological consensus of realizing national rejuvenation. The road of socialism with Chinese characteristics led by the CPC is the only way to realize the great rejuvenation of the Chinese nation.